2019
DOI: 10.1111/ajad.12925
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Low‐Barrier Buprenorphine Initiation Predicts Treatment Retention Among Latinx and Non‐Latinx Primary Care Patients

Abstract: Background and Objectives Patients are at risk of dropout while waiting for buprenorphine treatment. Study goals are to compare 3‐month retention in two different methods to buprenorphine initiation among persons with opioid use disorder. Methods We compared 3‐month treatment retention rates of low‐barrier buprenorphine initiation (i.e., rapid induction) (n =58) or a traditional method of buprenorphine initiation ( n = 45) for persons with opioid use disorder seen at an urban community health center. Results L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Removing regulatory barriers to expand naloxone and sterile syringe access through community-based distribution ( Davis & Carr, 2020 ) and through OTPs, which continued to dispense MOUD throughout the pandemic, could potentially address disparities by facilitating more efficient distribution through networks of patients and front-line treatment programs ( Collins et al, 2020 ). Conversely, implementing low-barrier access to MOUD, such as rapid or telehealth induction of suboxone treatment, in existing syringe or naloxone distribution programs could be another option to streamline access to essential services, as research has shown low-barrier services to be associated with reductions in racial/ethnic disparities in access to MOUD ( Lee et al, 2019 ). Offering harm reduction and MOUD services concurrently could potentially serve to address disproportionate systemic and structural barriers to care that marginalized MOUD patients experience.…”
Section: Discussionmentioning
confidence: 99%
“…Removing regulatory barriers to expand naloxone and sterile syringe access through community-based distribution ( Davis & Carr, 2020 ) and through OTPs, which continued to dispense MOUD throughout the pandemic, could potentially address disparities by facilitating more efficient distribution through networks of patients and front-line treatment programs ( Collins et al, 2020 ). Conversely, implementing low-barrier access to MOUD, such as rapid or telehealth induction of suboxone treatment, in existing syringe or naloxone distribution programs could be another option to streamline access to essential services, as research has shown low-barrier services to be associated with reductions in racial/ethnic disparities in access to MOUD ( Lee et al, 2019 ). Offering harm reduction and MOUD services concurrently could potentially serve to address disproportionate systemic and structural barriers to care that marginalized MOUD patients experience.…”
Section: Discussionmentioning
confidence: 99%
“…Low-threshold approaches to MAT have been associated with better retention in care [ 6 , 10 ]. This may be even more crucial for patients of racial minority backgrounds, for whom MAT retention has been shown to be lower, likely due to the impact of complex and interacting social determinants [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This transition to telehealth provided an opportunity to study the impact of a flexible, low-threshold model of audio-only telehealth care intended to increase treatment access for people with OUD [ 4 ]. Previous research shows that low-threshold treatment is associated with better retention overall, demonstrating the importance of ongoing consideration of this model beyond the pandemic [ 6 ]. This case study outlines the organizational telehealth adaptations that enabled virtual counseling, peer support, therapy groups, and clinical care during COVID-19 in this community-based MAT program.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, low threshold programs generally prioritize harm reduction, do not require counseling and do not exclude patients from treatment if there is ongoing drug or alcohol use (Jakubowski & Fox, 2019). Low barrier addiction clinics have been shown to facilitate prescription of evidence based pharmacotherapy as well as reduce substance use and improve treatment retention (Lee et al, 2019;Wiercigroch et al, 2020). Patients report positive experiences at these clinics and appreciate the emphasis on harm reduction (Snow et al, 2019).…”
Section: Introductionmentioning
confidence: 99%